Magnesium in acute pediatric asthma in the emergency department (MAGICIAN)—A multicentre randomized controlled clinical trial protocol - Suzanne Schuh; Sunita O’Shea; Stephen B. Freedman; Mohamed Eltorki; Jocelyn Gravel; Francine M. Ducharme; Waleed Alqurashi; Roger Zemek; George Wells; Jesse Elliott; April Kam; Sarah Curtis; et al. (PLoS ONE, 2026)
Background While guidelines recommend intravenous magnesium (IVMg) for refractory pediatric acute asthma, evidence for benefit is scant and disparate. IVMg therapy is resource-intensive and can cause hypotension. To determine if IVMg alters the exacerbation course, it must be given early , and the clinical effect measured at the peak effect of routine co-interventions. Primary aim In children with acute asthma remaining in moderate-severe respiratory distress after initial ED therapy, to determine if early IVMg therapy is associated with a significantly greater improvement in respiratory distress at 2 hours after starting IVMg, compared to placebo. Hypothesis IVMg will yield significantly greater Pediatric Respiratory Assessment Measure (PRAM) improvement of ≥1.0 point than placebo. Study design A randomized double-blind placebo-controlled trial in 6 Canadian pediatric EDs of otherwise healthy children 2–17 years old with acute asthma and PRAM ≥5 after initial 1 hour therapy with systemic corticosteroids and 3 inhaled salbutamol ± ipratropium treatments. Intervention IVMg sulfate (75 mg/kg, max 2.5 g) or normal saline placebo over 30 minutes. Primary outcome PRAM 2 hours post-intervention start. Secondary: PRAM ≤3 at 2 hours; change in PRAM and vital signs over 3 hours; hospitalization; asthma re-visits by 72 hours. Sample size With 192 patients, a two-sided test and alpha 0.05 have 80% power to achieve statistical significance if IVMg yields a difference in PRAM changes ≥1.0 point between groups. Primary analysis Student’s t test comparing a difference in PRAM changes between groups. Expected outcomes This trial will clarify if there is an incremental clinical benefit of IVMg in pediatric refractory asthma. A positive result will establish a proven routine standard of care for this indication; a negative result will lead to de-implementation of IVMg which may also lead to cost savings. Status Enrolling at SickKids and McMaster, start of other sites pending. No results generated yet. Study title Magnesium Trial in Acute Asthma in Emergency Department